2005
DOI: 10.1136/pgmj.2004.023028
|View full text |Cite
|
Sign up to set email alerts
|

Substance misuse in the older population

Abstract: Substance misuse among the older population is largely overlooked and underreported. Many factors contribute to this, not least the fact that presentation may be atypical and hence easily missed by the medical practitioner. There may be many clues to its existence, provided the physician remains alert to these. Despite this it is quite comforting to know that once identified, the evidence to date suggests that older people may respond at least as well as younger people to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…Further, the alcohol dependence rate among Korean elderly immigrants in this study was also substantially higher than what has appeared in other literature. For example, a study conducted in Britain reported that alcohol dependence rates among those aged 65 to 69 and 70 to 75 were 1.7% and .9%, respectively (McGrath et al 2005), whereas in the U.S., the rate for the elderly age 65 and older was 2-4% (Adams et al 1993). Taken at face value, elderly Korean immigrants have a higher prevalence of drinking problems than do their homeland counterparts as well as in comparison to the elderly U.S. population and that of industrial countries such as Great Britain.…”
Section: Korean Immigrants and Alcohol Usementioning
confidence: 95%
“…Further, the alcohol dependence rate among Korean elderly immigrants in this study was also substantially higher than what has appeared in other literature. For example, a study conducted in Britain reported that alcohol dependence rates among those aged 65 to 69 and 70 to 75 were 1.7% and .9%, respectively (McGrath et al 2005), whereas in the U.S., the rate for the elderly age 65 and older was 2-4% (Adams et al 1993). Taken at face value, elderly Korean immigrants have a higher prevalence of drinking problems than do their homeland counterparts as well as in comparison to the elderly U.S. population and that of industrial countries such as Great Britain.…”
Section: Korean Immigrants and Alcohol Usementioning
confidence: 95%
“…The importance of brief interventions, screening and the early identification of alcohol misuse for older adults continues to be recognized [40,41]. A number of recent research papers have pointed out differences in the presentation of at-risk drinking in older adults compared with younger individuals [41] and the uptake of aftercare services [42].…”
Section: Alcohol Interventions In Older Adultsmentioning
confidence: 98%
“…6 Older people not only receive most of the prescriptions in the UK but are also being dispensed multiple medications. 7 Over-the-counter availability (or methods of obtaining medicines other than through legitimate channels) makes multiple analgesic drug use a particular problem. 8 A very interesting study has drawn attention to the finding that 40% of elderly primary care patients on low-dose opioid analgesics for a year fulfilled the Research Diagnostic Criteria for dependence syndrome.…”
Section: Prescribed Medicationsmentioning
confidence: 99%